2000
DOI: 10.1021/ac000665j
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed Flow Modulation for High-Speed GC Using a Pressure-Tunable Column Ensemble

Abstract: A computer-driven pressure controller is used to deliver pressure pulses to the junction point of two series-coupled columns using different stationary-phase chemistries. The column ensemble consists of a trifluoropropylmethyl polysiloxane column followed by a dimethyl polysiloxane column. Each pressure pulse causes a differential change in the carrier gas velocities in the two columns, which lasts for the duration of the pulse. A pressure pulse is used to selectively increase the separation of a component pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 21 publications
0
24
0
Order By: Relevance
“…The fast GC-TOFMS (time-of-flight MS) analysis of a grapefruit essential oil, using a 14 m6180 lm capillary column ensemble, which was temperature programmed at 50 K/min, was reported recently [4]. The analysis of the volatile essential oil fraction was completed within 200 s; however, the chromatogram contained severely overlapping peaks, and the authors relied on pressure tuning and mass-spectral deconvolution to identify and quantify individual components.…”
Section: Introductionmentioning
confidence: 99%
“…The fast GC-TOFMS (time-of-flight MS) analysis of a grapefruit essential oil, using a 14 m6180 lm capillary column ensemble, which was temperature programmed at 50 K/min, was reported recently [4]. The analysis of the volatile essential oil fraction was completed within 200 s; however, the chromatogram contained severely overlapping peaks, and the authors relied on pressure tuning and mass-spectral deconvolution to identify and quantify individual components.…”
Section: Introductionmentioning
confidence: 99%
“…The latter reports essential information relative to each application, which will not be repeated in this section (more details may be derived by directly consulting the reference). In the field of narrow-bore column fast GC research, a total of 18 essential oil applications are reported [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43]; Table 1 also reports the use of a short conventional column in fast GC essential oil analysis [9], while eight are focussed on fatty acid methyl ester (FAME) analysis [44][45][46][47][48][49][50][51]; single works regard triglycerides [52] and an alcoholic beverage [53]. More detailed information will be provided hereafter for some of the most representative high-speed GC examples.…”
Section: Narrow-bore Columnsmentioning
confidence: 99%
“…The pneumatic valve is operated by a 50-55 psig compressed air source (1 psi = 6894.76 pa), connected through an electronically-actuated solenoid valve (Model GH3412, Precision Dynamics, Phoenix, AZ, USA). The configuration of the system is described in greater detail in [6]. Ballast chamber pressure is controlled by an electronic pressure controller (MKS Model 640 A, MKS Instruments, Andover, MA).…”
Section: Materials and Proceduresmentioning
confidence: 99%
“…A flow-modulation technique has been described in detail by Sacks et al [3][4][5][6], and has been applied to complex mixtures such as chlorinated pesticides and essential oils [7][8][9]. This technique is performed by programming the carrier gas pressure at the junction point of a series-coupled (tandem) ensemble of capillary columns that exhibit differing selectivity for the target compounds to be analyzed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation